INTERPRETASI NURCHOLISH MADJID ATAS AYAT-AYAT AL-QUR’AN TENTANG PLURALISME AGAMA - Muhyidin Azmi (Sekolah Tinggi Agama Islam Sadra, 2023)
This research aims to reveal the concept of religious pluralism expressed by Nurcholish Madjid in his renewal ideas and Nurcholish Madjid's interpretation of the verses of the Qur’an about religious pluralism is like. This research is library research is research that makes books that discuss the themes studied as a source of data in research. The object to be studied in this research is Nurcholish Madjid. The results of this study indicate that religious pluralism in the idea of Nurcholish Madjid is a plurality of paths leading to one truth, namely the truth of God. This is based on his belief that the One Truth is only God, so only God cannot be more than one, while the path to God as the One Truth certainly varies, according to human ability to obtain and reason information from the procedures to God. Nurcholish Madjid, interprets religious pluralism from two contexts, namely, First, the Indonesian context and modernity. Second, the context of the meaning of the word al-Islām